Inovasi dan Kemasan Produk UMKM dengan Memanfaatkan Ekosistem Digital untuk Meningkatkan Sales di Kota Sukabumi - Djaddang, Syahril; Nawasiah, Nana; Wijaya, Agustinus Miranda; Syam, M. Ardiansyah; Sari, Lola Fitria; Riskarini, Dian (Penerbit Goodwood, 2024)
Purpose: Community Service aims to train and assist in the digital marketing Android-based MSME products after the COVID-19 pandemic. Methodology: The PkM method used was FGD, interviews, and random sampling from MSMEs in Sukabumi. Assistance with the digitalization of MSME products, and as a basis for implementing Android-based digital marketing for MSME products with marketing applications in marketplaces, such as; Lasada, Shoopee, and IG to increase sales for MSMEs in the city of Sukabumi Results: The results of this PkM are expected to be used to develop digital marketing for Android-based MSME products. PkM is important for creating the digitalization of MSME products and building society's entrepreneurial spirit. Limitations: By utilizing the digital ecosystem, MSMEs in Sukabumi City can overcome several existing limitations and open up opportunities to increase sales in local and wider markets. Contribution: The Pancasila University Jakarta Postgraduate School Abdimas Team together with Muhammadiyah University Sukabumi (UMMI) and Sukabumi MSMEs carried out community service with the theme